2019
DOI: 10.1557/mrs.2019.122
|View full text |Cite
|
Sign up to set email alerts
|

Insights into tribology from in situ nanoscale experiments

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 101 publications
0
25
0
Order By: Relevance
“…Piezo/triboelectric applications are also important energy applications for the transfer of kinetic energy into electricity, and the conversion of sea wave motions to electricity can be regarded as blue energy . In situ TEM has been reported to reveal the physics of piezoelectric phenomena, but one may expect more triboelectric experiments to be performed by in situ TEM in the nearest future …”
Section: Conclusion and Trendsmentioning
confidence: 99%
“…Piezo/triboelectric applications are also important energy applications for the transfer of kinetic energy into electricity, and the conversion of sea wave motions to electricity can be regarded as blue energy . In situ TEM has been reported to reveal the physics of piezoelectric phenomena, but one may expect more triboelectric experiments to be performed by in situ TEM in the nearest future …”
Section: Conclusion and Trendsmentioning
confidence: 99%
“…Insights into nanotribology from in situ experiments have enabled identification of physical processes occurring at and below a wear surface. In their article in this issue, Jacobs et al 31 describe key advances in in situ nanotribology that have enabled direct observations of processes in the sliding contact, including tribochemistry and subsurface deformation. For example, in situ TEM nanotribology has revealed a number of material transformations in layered materials typically used as lubricants such as MoS 2 32 and graphite.…”
Section: Nanotribologymentioning
confidence: 99%
“…Subsurface dislocation processes in metal contacts during in situ nanotribology demonstrate the impact of in situ testing, and surface adhesion phenomena are readily observed with in situ TEM. As Jacobs et al 31 discuss, breakthroughs in in situ nanotribological characterization have the potential to impact a wide array of applications and technologies.…”
Section: Nanotribologymentioning
confidence: 99%
“…17 Gosvami et al 29 suggested that wear became significant above 5 GPa in their experiments, but it is quite likely that some of the tribofilm is removed by the hard AFM tip during the early stages of tribofilm formation (where the film is less durable 22 ) even at lower pressures. Although AFM experiments allow topographic images to be obtained frequently during the tribofilm growth process, 28 direct asperity contact may remove some material even within a single scanning cycle. If the tribofilm is being both formed and partially removed during the rubbing process, this clearly complicates any subsequent kinetic analysis.…”
Section: Introductionmentioning
confidence: 99%